Developing Sharia Economic Instrument for Indonesia-Malaysia Hajj Service System: Maqâshid al-Syarî`ah Perspective - Masse, Rahman Ambo; Aderus, Andi; Halidin, Ali (Madania: Jurnal Kajian Keislaman, 2021)
This study aims to analyze the hajj services of the Ministry of Religious Affairs of the Republic of Indonesia and the Malaysian Hajj Savings Institute from the maqâshid al-syarî`ah aspect. This study used a qualitative method with a phenomenological approach. The data was obtained through interviews and documents. The data was analyzed through a process of extension of observation and triangulation of sources as well as techniques between interview data and documents. This data was then discussed and analyzed using the maqâshid al-syarî`ah approach. Aspects of the hajj service of the Ministry of Religious Affairs of the Republic of Indonesia and the Malaysian Hajj Savings Institute here include aspects of the intensity of the guidance of the hajj rituals that have been in accordance with the maqâshid al-syarî`ah in the aspects of hifdz al-dîn and hifdz al-`irdh. Hotel accommodation services are in accordance with the aspects of hifdz al-`aql, hifdz al-ruh, and hifdz al-`irdh. Consumption services are in accordance with the aspects of hifdz al-nafs and hifdz al-`aql. Meanwhile, health services are in accordance with the aspects of hifdz al-nafs. Penelitian ini bertujuan untuk menganalisis pelayanan haji kementerian Agama Republik Indonesia dan Lembaga Tabung Haji Malaysia dari aspek  maqâshid al-syarî`ah. Penelitian ini menggunakan metode kualitatif dengan pendekatan fenomenologis. Data diperoleh melalui wawancara dan dokumen. Data dianalisis melalui proses perpanjangan pengamatan dan triangulasi sumber maupun teknik antara data wawancara dan dokumen. Data ini kemudian dibahas dan dianalisis dengan pendekatan maqâshid al-syarî`ah. Aspek pelayanan haji Kementerian Agama RI dan Lembaga Tabung Haji Malaysia meliputi aspek intensitas pembimbingan manasik haji telah bersesuaian dengan maqâshid al-syarî`ah pada aspek hifdz al-dîn dan hifdz al-`irdh. Pelayanan akomodasi perhotelan bersesuaian dengan aspek hifdz al-`aql, hifdz al-ruh, dan hifdz al-`irdh.  Pelayanan konsumsi bersesuaian dengan aspek hifdz al-nafs dan hifdz al-`aql. Sedangkan pelayanan kesehatan bersesuaian dengan aspek hifdz al-nafs.